Study the effect of TIO2 and soaking time to the natural hydroxyapatite properties - Shahrizal, M. H.; Sri Asliza, Md Amin; Mohd Nazree, Derman; Mohd Zaheruddin, Kasmuin (Universiti Sains Malaysia (USM), 2011)
Organized by Universiti Sains Malaysia (USM), 24th - 27th May 2006 at Universiti Sains Malaysia (USM), Penang, Malaysia.